Typology in juvenile delinquency: A literature review - Sette Galinari, Lais (2020)
The delinquent behavior of adolescents can develop in different trajectories. Many researchers sought to understand differences in terms of types/ profiles. A difficulty in this field is the lack of systematization of the results previously found, this study aimed to carry out a review of the literature, analyzing the studies that sought to find profiles among the juvenile offenders. A search was performed on PsycInfo, Web of Science and Scielo databases and 56 studies were selected. The studies found profiles considering risk/protection factors, criminal trajectories and psychological characteristics. The review pointed out that it is necessary to clarify the aspects that are relevant in relation to the delimitation of profiles and in how this knowledge could be applied in practice.